Long‐term changes in hypoxia and soluble reactive phosphorus in the hypolimnion of a large temperate lake: consequences of a climate regime shift. (20th January 2014) - North, Ryan P.; North, Rebecca L.; Livingstone, David M.; Köster, Oliver; Kipfer, Rolf
Abstract The (Lower) Lake of Zurich provides an ideal system for studying the long‐term impact of environmental change on deep‐water hypoxia because of its sensitivity to climatic forcing, its history of eutrophication and subsequent oligotrophication, and the quality and length of its data set. Based on 39 years (1972–2010) of measured profiles of temperature, oxygen concentration and phosphorus (P) concentration, the potentially confounding effects of oligotrophication and climatic forcing on the occurrence and extent of deep‐water hypoxia in the lake were investigated. The time‐series of Nürnberg's hypoxic factor (HF) for the lake can be divided into three distinct segments: (i) a segment of consistently low HF from 1972 to the late‐1980s climate regime shift (CRS); (ii) a transitional segment between the late‐1980s CRS and approximately 2000 within which the HF was highly variable; and (iii) a segment of consistently high HF thereafter. The increase in hypoxia during the study period was not a consequence of a change in trophic status, as the lake underwent oligotrophication as a result of reduced external P loading during this time. Instead, wavelet analysis suggests that changes in the lake's mixing regime, initiated by the late‐1980s CRS, ultimately led to a delayed but abrupt decrease in the deep‐water oxygen concentration, resulting in a general expansion of the hypoxic zone in autumn. Even after detrending to remove long‐term effects, the concentration of soluble reactive P in the bottom water of the lake was highly correlated with various measures of hypoxia, providing quantitative evidence supporting the probable effect of hypoxia on internal P loading. Such climate‐induced, ecosystem‐scale changes, which may result in undesirable effects such as a decline in water quality and a reduction in coldwater fish habitats, provide further evidence for the vulnerability of large temperate lakes to predicted increases in global air temperature.